2019
DOI: 10.1186/s12860-019-0205-4
|View full text |Cite
|
Sign up to set email alerts
|

An Electron paramagnetic resonance (EPR) spin labeling study in HT-29 Colon adenocarcinoma cells after Hypericin-mediated photodynamic therapy

Abstract: Background Colon cancer affects 1.23 million people worldwide and is the third most common malignant disease in men and the second in women. The only curative treatment is surgical resection, but a significant number of patients develop local recurrence or distant metastases. One of the alternative treatment methods for colon cancer is photodynamic therapy (PDT). In recent years, hypericin (HYP) derived from Hypericum perforatum has been suggested as a strong candidate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yonar et al investigated HY-PDT-induced biophysical changes in colon cancer cells, which agree with our observation of HY accumulation in colon cancer cells. 51 In their study, HT-29 colon adenocarcinoma cells were subjected to HY-PDT at HY concentrations of 0.04, 0.08, and 0.15 µM. Electron paramagnetic resonance (EPR) spectra of spin-labeled adenocarcinoma cells were evaluated post HY-PDT with the EPRSIMC program demonstrating concentration-dependent changes in the domain parameters that indicated an increase in HY concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Yonar et al investigated HY-PDT-induced biophysical changes in colon cancer cells, which agree with our observation of HY accumulation in colon cancer cells. 51 In their study, HT-29 colon adenocarcinoma cells were subjected to HY-PDT at HY concentrations of 0.04, 0.08, and 0.15 µM. Electron paramagnetic resonance (EPR) spectra of spin-labeled adenocarcinoma cells were evaluated post HY-PDT with the EPRSIMC program demonstrating concentration-dependent changes in the domain parameters that indicated an increase in HY concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro and in vivo studies reported that hypericin PS activated at 594 nm could destroy cancer cell proliferation effectively. The researchers already demonstrated that the effect of herbal extracts combined with illumination could significantly reduce cancer development by prohibiting metabolic viability and proliferation cancer cells [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%